PROBLEMS OF ARCHITECTURAL FORMATION OF REHABILITATION COMPLEXES FOR MILITARY PERSONNEL - Hniezdilov, Serhii; Zhovkva, Olga (Theory and practice of design, 2023)
This article focuses on the study and analysis of the main challenges that arise during the architectural formation of rehabilitation complexes for military personnel. Particular attention is paid to such aspects as the implementation of multifunctionality, flexible planning, environmental friendliness and modern interpretation. The main requirements are defined, which must be taken into account when designing an architectural environment for the physical and psychological rehabilitation of military personnel. Goal. The purpose of this article is to research and reveal the main aspects of designing rehabilitation complexes for military personnel, taking into account modern requirements and needs of society, in order to determine the main approaches and principles in creating functional, comfortable and aesthetically attractive complexes of this type. Methodology. The following methods are used in this article: analysis of international experience and data collection, which will allow understanding modern trends in the architecture of physical and psychological rehabilitation complexes; review of available studies on the design of these complexes; performing architectural analysis and modeling, including functional and spatial analysis, for the development of optimal design solutions. These research methods will contribute to the collection, analysis and interpretation of data necessary to achieve the purpose of the article and solve the tasks. Result. As a result of the study, the main problems in the formation of architectural solutions for rehabilitation complexes for military personnel were described, and the main principles in their design were also formulated. The main features and trends necessary for the architectural and planning solution of this type of building have been identified. In order to fully understand this issue, scientific materials on this topic were used in the study. Scientific novelty. The analysis and description of the main problems in the architectural formation of rehabilitation complexes was carried out. The main features and principles necessary for the design of these complexes were considered and improved. Practical significance. The results of the research are a valuable contribution to the further development of rehabilitation-type facilities, as they have practical recommendations that will become appropriate for obtaining a result. The considered issues and features in the architectural formation of rehabilitation complexes for military personnel play an important role in creating an effective environment during their design. These recommendations will help to develop an architectural organization for complexes of this type, taking into account all factors and factors necessary for the implementation of a high-quality and effective rehabilitation process.